Delay in diagnosis of congenital anal stenosis - Elroy P. Weledji; Motaze Sinju (Elsevier, 2016)
Although a minor anorectal malformation the delay in diagnosis and treatment of anal stenosis may result in significant early or late complications. Early inspection of the perineum in the neonate to pick up and correct anorectal malformation improves long term outcome but this requires proper anal examination or it could be missed. We present and discuss a case of delayed diagnosis of congenital anal stenosis (a low anorectal anomaly) with an imminent colonic perforation. Severe anal stenosis will always require examination under anesthesia with graded Hegar's dilatation followed by postoperative maintenance. The Hegar dilator is thus both diagnostic and therapeutic in congenital anal stenosis.